Direct and transdentinal antibacterial activity of chlorhexidine - Lessa, Fernanda Campos Rosetti; Nogueira, Indri; Da Silveira Vargas, Fernanda; Spolidorio, Denise Magdalena Palomari; Hebling, Josimeri; García-Godoy, Franklin; De Souza Costa, Carlos Alberto [UNESP] (My University, 2010)
Purpose: To evaluate the antibacterial effect of different Chlorhexidine (CHX) concentrations against Streptococcus mutans using the agar-diffusion method with and without human dentin discs placed between the bacteria and the test substances. Methods: For the direct application (agar-well technique), a base layer containing 15 mL of BHI agar and 300 uL of S. mutans inoculum (109 cfu/mL) was prepared in Petri dishes. Six wells per dish were made at equidistant points and immediately filled with CHX gels (0.12%, 0.2%, 1% and 2%), 35% phosphoric acid and pure natrosol (n=6 wells/substance). Paper discs soaked in sterile distilled water served as control group (n=6). For the indirect application (transdentinal diffusion), 0.2 mm- and 0.5 mm-thick human dentin discs (36 discs/thickness) had the hydraulic conductance determined, which allowed the homogeneous allocation of them to the experimental and control groups. The discs were placed at equidistant points on the Petri dishes containing BHI with the S. mutans inoculum (six discs per dish; one per substance) with the pulpal side in contact with the bacteria. In the discs treated with CHX gels, dentin surface was etched with H3PO 4 and rinsed with distilled water before CHX gel application for 1 minute. After both direct and indirect application, the dishes were incubated for 24 hours and the bacterial growth inhibition zones formed around the wells and dentin discs were measured. Data were analyzed statistically by the non-parametric Kruskal-Wallis and Mann-Whitney tests at 5% significance level. Results: In the direct test, all CHX concentrations presented a dose-dependent antibacterial activity against S. mutans. In the indirect test, there were statistically significant differences (P< 0.05) among all groups and the largest microbial growth inhibition zones were observed when 2% CHX was applied on 0.2 mm-thick discs (P< 0.05). It was concluded that all evaluated CHX gels exhibited both direct and transdentinal antibacterial activity against S. mutans. This effect of CHX was strongly influenced by the CHX concentration as well as the dentin barrier thickness.